Improvement of Road Tunnel Ventilation through Predictive Control - Hrbcek, Jozef; Janota, Ales (Communications - Scientific letters of the University of Zilina, 2008)
Design of an effective ventilation system for the road tunnel is usually a challenging task whose solution is less or more tending to optimum. Predictive control seems to be apromising approach that can help to improve properties of existing ventilation systems applied in road tunnels. Advantages of predictive control result mainly from its ability to solve both SISO and MIMO tasks, to have regard for dynamics of process changes in a broad extent, to compensate effect of measurable and non-measurable failures and to formulate the task as an ”optimization control task“ considering limiting conditions of control actions, changes of control actions and output variables. Data characterising the existing ventilation system can be used to analyse and identify the system and create its stochastic model. Thereafter the predictive control of ventilation can be designed enabling to predict concentrations of pollutants and optimize system operation.